Knowledge and Attitudes of Turkish Physicians About Organ Donation After Circulatory Death - Pınar Ayvat (Galenos Yayinevi, 2023)
Objective: Organ donation (OD) still cannot reach the desired level in our country. A new form of OD is being implemented in the world. OD can be performed with family consent from patients with circulatory death (CD). This study was conducted to measure the attitudes and knowledge levels of Turkish physicians about organ donation after circulatory death (DCD). Materials and Methods: Three-part survey questions were sent to specialist physicians via e-mail. In the first part, their sociodemographic characteristics, in the second part their attitudes and behaviors about OD, and in the third part, their knowledge levels about DCD were measured. Results: 51.9% of the 258 participants were female and 48.1% were male. 52.3% specialized in surgery, 47.7% specialized in internal medicine. 39.1% were working in the intensive care unit, 25.9% were working in the emergency room, and 21.3% were working in the operating room. All physicians agreed on the importance of OD. Although OD rates were low, this rate was found to be significantly higher in surgical branches compared with internal branches (p=0.02). Most organ donors shared this situation with their families (respectively, surgical physicians 83.3%, internal physicians 66.6%). The percentage of surgical branches receiving education on brain death or organ transplantation was high. However, the definition of DCD in both groups was little known (2.9%, 0.8%, respectively). When their knowledge levels were examined, only five questions (these were propositions about OD and donor care) were higher for the surgical physicians to answer correctly. Theoretical knowledge propositions about CD were answered incorrectly in both groups. Conclusion: To increase the awareness of Turkish physicians about DCD, which has been known since 1995, there is a need for new research and medical education to include current issues. Therefore, as soon as the legislation is enacted in our country, the number of ODs will increase.